Effects of Northern Bobwhite Habitat Management Practices on Red Imported Fire Ants - Shaun Williamson; L. Wes Burger Jr.; Stephen Demarais; Michael Chamberlain (National Quail Symposium Proceedings, 2017)
Management practices that create early successional plant communities through disturbance (discing and prescribed fire) often are prescribed for restoration of declining northern bobwhite (Colinus virginianus) populations. Because disturbance may facilitate invasion of exotic flora and fauna such as red imported fire ants (RIFA, Solenopsis invicta), we hypothesized that habitat management practices commonly used to enhance bobwhite habitat might have the unintended consequence of increasing local abundance of RIFA. During 1999, we tested effects of 4 treatments (spring discing, spring prescribed burning, spring mowing, and no management), in a randomized complete block design (n = 10) on RIFA abundance in Conservation Reserve Program (CRP) fields in central Mississippi. We surveyed RIFA abundance using 3 measures: 1) mound density, 2) a population index based on worker ant and brood estimates, and 3) foraging activity as indexed by attraction to protein bait cups. During May 1999, mound density (P = 0.0136) and population index (P 0.0078) differed among treatments, with abundance values greatest in plots treated with fire, and lowest in disced plots. The index of foraging activity did not differ among treatments (P = 0.6637). During October 1999, mound density (P = 0.0334) and population index (P = 0.0451) differed among treatments with abundance values greatest in plots receiving fire and disc treatments, and lowest abundance in control plots. The index of foraging activity did not differ among treatments (P = 0.9079). Disturbance tools such as prescribed fire and discing are essential to maintain plant communities to which bobwhite are adapted; however, they may have the unintended consequence of facilitating invasion of RIFA and increasing local RIFA populations.
Keywords: Colinus virginianus; discing; fire ant; habitat management; northern bobwhite; prescribed burning; Solenopsis invicta